Where's God when I'm scared - Ellis, Robert; Vischer, Phil.; Olsen, Chris; Everland Entertainment; Word Records & Music; Big Idea Productions (Burbank, CA : Warner Home Video, 2003)
Two animated stories that teach children a Biblical perspective on handling everyday fears.
Tales from the crisper / directed & animated by Chris Olsen; written by Phil Vischer; created by Phil Vischer and Mike Nawrocki -- Daniel and the lions' den / written and directed by Phil Vischer.
Videodisc release of the 1993 productions.
Special features: audio commentary, kids commentary, what's the big idea?, art for the sake of impact, art and audience. Fun: peas and thank you storybook, how to draw the Closet Monster, how to draw Frankencelery, family fun activity, Veggie karaoke, trivia, DVD-ROM fun.
Animators, Robert Ellis, Chris Olsen, Phil Vischer.
Voices (Tales from the crisper): Dan Anderson, Gail Freeman, Michael Nawrocki, Lisa Vischer, Phil Vischer. (Daniel and the lions' den): Gail Freeman, Michael Nawrocki, Mike Sage, Phil Vischer ; narrator: Gail Freeman.
Voices (Daniel and the lions' den): Gail Freeman, Michael Nawrocki, Mike Sage, Phil Vischer; narrator: Gail Freeman.
DVD; 2.0 stereo.
Keywords: Christian life -- Juvenile films; Fear in children -- Juvenile films; Fear -- Religious aspects -- Christianity -- Juvenile films; Animated films; Children's films